Patterns of drug preference and use among people who inject drugs in Melbourne, Australia. (27th November 2015) - Scott, Nick; Caulkins, Jonathan P.; Ritter, Alison; Dietze, Paul
Abstract: Background : Understanding of substitution patterns in drug using careers is limited. Between 2009 and mid-2013, the purity-adjusted price of methamphetamine declined sharply in Melbourne in absolute terms and relative to the purity-adjusted price of heroin. We determine whether there were associated increases among people who inject drugs (PWID) in (1) use of methamphetamine and (2) citing methamphetamine as the drug of choice. Method : Responses to "drug of choice" and "most used drug" were obtained from baseline and follow-up interviews of the 688 PWID enrolled in the Melbourne Injecting Drug User Cohort Study between April 2008 and August 2013, categorised as heroin, methamphetamine, cannabis or other. Previous month heroin and methamphetamine use was reported at baseline by 82% and 41% of participants, respectively, and 51% had completed four or more interviews in this period. A Markov model that included marginal effects for methamphetamine purity-adjusted price was used to calculate (1) transitions between drug of choice and (2) conditional probabilities for most used drug. Parameters were determined by fitting multinomial logistic models to appropriate data subsets. Results : At baseline, the majority of participants reported heroin as both their preferred drug and the drug they used most. There were no significant increases in reports of methamphetamine as drug of choice, or as the most used drug. Conclusion : In a cohort of PWID who reported a range of drug behaviours, there was little evidence of drug substitution into methamphetamine, despite substantial declines in its purity-adjusted price.